Supercontinuum generation in three-fold symmetry microstructured fibers in visible and infrared spectral regions - Holdynski, Zbyszek; Napierala, Marek; Jozwik, Michalina; Szostkiewicz, Lukasz; Mergo, Pawel; Nasilowski, Tomasz (Photonics Letters of Poland, 2016)
We present a series of three fold symmetric silica microstructured fibers for nonlinear application. The fibers are designed to have zero dispersion wavelength far from the pump wavelength. In our fibers a domination of nonlinear effects is precisely controlled by selectively increased three air holes in the vicinity of the core. Our fibers allow for the broadband single mode spectrum generation and the achievement of flat spectra even after changes of fiber dispersion caused by fabrication inaccuracies. Full Text: PDF References S. T. S?rensen, C. Larsen, C. Jakobsen, C. L. Thomsen, and O. Bang, "Single-mode pumped high air-fill fraction photonic crystal fiber taper for high-power deep-blue supercontinuum sources", Opt. Lett, 39, 1097 (2014). CrossRef V. Couderc, P. Leproux, V. Tombelaine, L. Grossard, and A. Barthélémy, "Raman cascade suppression by using wide band parametric conversion in large normal dispersion regime", Opt. Express, 13, 8584 (2005). CrossRef H. E. Heidepriem, S. C. W. Smith, and T. M. Monro, "Suspended nanowires: Fabrication, design and characterization of fibers with nanoscale cores", Opt. Express, 17, 2646 (2009). CrossRef U. M?ller, Y. Yu, I. Kubat, C. R. Petersen, X. Gai, L. Brilland, D. M´echin, C. Caillaud, J. Troles, B. Davies, and O. Bang, "Multi-milliwatt mid-infrared supercontinuum generation in a suspended core chalcogenide fiber", Opt. Express, 17, 3282 (2015). CrossRef I. Shavrin, S. Novotny, and H. Ludvigsen, "Mode excitation and supercontinuum generation in a few-mode suspended-core fiber", Opt. Express, 21, 32141 (2013). CrossRef M. Klimczak, G. Stepniewski, H. Bookey, A. Szolno, R. Stepien, D. Pysz, A. Kar, A. Waddie, M. R. Taghizadeh, and R. Buczynski, "Broadband infrared supercontinuum generation in hexagonal-lattice tellurite photonic crystal fiber with dispersion optimized for pumping near 1560??nm: reply", Opt. Lett. 39, 2241 (2014). CrossRef X. Zhang, X. Zhu, X. Chen, H. Li, J. Peng, N. Dai, and J. Li, "A hollow beam supercontinuum generation by the supermode superposition in a GeO2 doped triangular-core photonic crystal fiber", Opt. Express, 20, 19799 (2012). CrossRef C. Lesvigne, V. Couderc, A. Tonello, P. Leproux, A. Barthélémy, S. Lacroix, F. Druon, P. Blandin, M. Hanna, and P. Georges, "Visible supercontinuum generation controlled by intermodal four-wave mixing in microstructured fiber", Opt. Lett, 32, 2173 (2007). CrossRef S. T. S?rensen, U. M?ller, C. Larsen, P. M. Moselund, C. Jakobsen, J. Johansen, T. V. Andersen, C. L. Thomsen, and O. Bang, "Deep-blue supercontinnum sources with optimum taper profiles ? verification of GAM", Opt. Express, 20, 10635 (2012). CrossRef A. Kudlinski, M. Lelek, B. Barviau, L. Audry, and A. Mussot, "Efficient blue conversion from a 1064 nm microchip laser in long photonic crystal fiber tapers for fluorescence microscopy", Opt. Express, 18, 16640 (2010). CrossRef A. Kudlinski, G. Bouwmans, O. Vanvincq, Y. Quiquempois, A. Le Rouge, L. Bigot, G. Mélin, and A. Mussot, "White-light cw-pumped supercontinuum generation in highly GeO2 -doped-core photonic crystal fibers", Opt. Lett. 34, 3631 (2009). CrossRef A. Kudlinski, V. Pureur, G. Bouwmans, and A. Mussot, "Experimental investigation of combined four-wave mixing and Raman effect in the normal dispersion regime of a photonic crystal fiber", Opt. Lett. 33, 2488 (2008). CrossRef Z. Holdynski, M. Napierala, P. Mergo, and T. Nasilowski, "Experimental Investigation of Supercontinuum Generation in Photonic Crystal Fibers Pumped With Sub-ns Pulses", J. Lightwave Technol., 33, 2106 (2015). CrossRef U. M?ller, S. T. S?rensen, C. Larsen, P. M. Moselund, C. Jakobsen ,J. Johansen, C. L. Thomsen, O. Bang, "Optimum PCF tapers for blue-enhanced supercontinuum sources", Opt. Fiber Technol., 18, 3104 (2012). CrossRef